Teabooma secunda (Hemiptera: Heteroptera: Cydnidae)—a new species of a New Caledonian endemic genus, with a redescription of T. princeps Distant - Lis, Jerzy A.; Lis, Barbara (Zootaxa, 2010)
Teabooma secunda sp. nov., the second species of a New Caledonian endemic genus, is described, illustrated, and compared with T. princeps Distant, 1914. Additionally, the latter is redescribed on the basis of its lectotype and seven other specimens.